O discurso midiático e a representação da causa indígena no Brasil - Anderson, Jaqueline Tavares (2023)
Brazil is a country that was colonized by Europeans and, since then, there has been discrimination against indigenous peoples, they have been socially excluded, they have suffered physical and territorial violence, for the colonization process to be successful. The colonization ended in 1822, when there was the Proclamation of Brazil's Independence from Portugal, however discursive memories with colonial aspects remained present in Brazilian society, spreading through the media and influencing ideas collectively shared by society. In this context, our research proposes to understand the representation of the indigenous cause in reports about the 2022 Free Land Camp (Acampamento Terra Livre in Portuguese), through the analysis of reports published on news websites, about an event of vindication of the indigenous peoples, the Free Land Camp. Previous research has shown a stereotyped and racist image of the Indigenous being propagated by newspapers (BARBOSA, 2010), in addition to presenting silences and exclusions by the Pernambuco media (MELO, 2003) and a significant change in the way of representing the Indigenous people: the leaders, women, and young indigenous people began to occupy legitimate spaces of speech when comparing texts from the 2000s with news from the 1990s. The general objective of this work is to understand the representation of the indigenous cause in news about 2022 Free Land Camp, having as reference the theoretical and methodological Discourse Analysis of French orientation, based mainly on the authors Dominique Maingueneau, Eni Orlandi, and Michel Foucault. We also adhere to the decolonial research approach, based on Eduardo Galeano and Walter Mignolo, and, about Brazilian racism, we adopt the studies of Silvio Almeida and Lilia Schwarcz. The corpus of analysis is a set of sixteen journalistic articles about the 2022 Free Land Camp: three from Veja Magazine, three from the G1 portal, three from UOL, two from Folha de S. Paulo, and five from Forum Magazine. The articles were published in April 2022, from 04/04/2022 to 04/20/2022. The categories of analysis are direct and indirect quotations, words between quotation marks, metaphors and paraphrases. We used concepts such as interdiscursivity, discursive memory, the said, unsaid and silencing, as guides in the interpretation of the data. The analysis revealed that there are colonial discursive formations in the articles analyzed, but they also have decolonial aspects. Democratic and environmentalist speeches were also observed, but in smaller proportions. All the reports analyzed appropriated the event to talk about the 2022 presidential elections.